Effects of Lingonberry (Vaccinium vitis-idaea L.) Supplementation on Hepatic Gene Expression in High-Fat Diet Fed Mice - Riitta Ryyti (MDPI AG, 2021)
The prevalence of nonalcoholic fatty liver disease (NAFLD) is growing worldwide in association with Western-style diet and increasing obesity. Lingonberry (Vaccinium vitis-idaea L.) is rich in polyphenols and has been shown to attenuate adverse metabolic changes in obese liver. This paper investigated the effects of lingonberry supplementation on hepatic gene expression in high-fat diet induced obesity in a mouse model. C57BL/6N male mice were fed for six weeks with either a high-fat (HF) or low-fat (LF) diet (46% and 10% energy from fat, respectively) or HF diet supplemented with air-dried lingonberry powder (HF + LGB). HF diet induced a major phenotypic change in the liver, predominantly affecting genes involved in inflammation and in glucose and lipid metabolism. Lingonberry supplementation prevented the effect of HF diet on an array of genes (in total on 263 genes) associated particularly with lipid or glucose metabolic process (such as Mogat1, Plin4, Igfbp2), inflammatory/immune response or cell migration (such as Lcn2, Saa1, Saa2, Cxcl14, Gcp1, S100a10) and cell cycle regulation (such as Cdkn1a, Tubb2a, Tubb6). The present results suggest that lingonberry supplementation prevents HF diet-induced adverse changes in the liver that are known to predispose the development of NAFLD and its comorbidities. The findings encourage carrying out human intervention trials to confirm the results, with the aim of recommending the use of lingonberries as a part of healthy diet against obesity and its hepatic and metabolic comorbidities.